2019
DOI: 10.1101/773242
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PrimPol-dependent single-stranded gap formation mediates homologous recombination at bulky DNA adducts

Abstract: Obstacles on the DNA template can lead to DNA replication fork stalling and genomic rearrangements. RAD51-mediated homologous recombination (HR) can promote restart and repair of stalled forks, but also post-replicative repair once the obstacle has been bypassed. Bulky DNA adducts are important replication-blocking lesions induced by environmental carcinogens, but it is not known whether they activate HR directly at stalled forks, or at gaps left behind ongoing forks. Here we show that in mammalian cells, bulk… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Previous studies showed that FANCD2 can protect nascent DNA from degradation upon the replication stress. However, the major question is how FANCD2 protects the stalled fork and what structure it is being acted upon (Petermann et al, 2010; Piberger et al, 2019). To investigate this question, we first verified over-resection in FANCD2 deficient cells with RPA2 phosphorylation as a surrogate for measuring ssDNA arising during resection in the presence of HU.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that FANCD2 can protect nascent DNA from degradation upon the replication stress. However, the major question is how FANCD2 protects the stalled fork and what structure it is being acted upon (Petermann et al, 2010; Piberger et al, 2019). To investigate this question, we first verified over-resection in FANCD2 deficient cells with RPA2 phosphorylation as a surrogate for measuring ssDNA arising during resection in the presence of HU.…”
Section: Resultsmentioning
confidence: 99%
“…This effect could be entirely attributed to PrimPol The ICL-localized DNA fiber assay can be combined with S1 nuclease, which cleaves at ssDNA gaps and has been used to evaluate repriming events in other contexts (e.g. Bai et al, 2020;Piberger et al, 2020;Quinet et al, 2020). As expected if ssDNA was generated after the lesion, S1 eliminated many IdU tracks downstream of ICLs, resulting in an apparent decrease of traverse reactions and a concomitant increase in the frequency of apparently stalled forks (Fig 3D and E).…”
Section: Primpol Engages In Repriming Reactions At Iclsmentioning
confidence: 99%
“…PRIMPOL promotes DNA repriming downstream of a lesion or replication block to facilitate fork restart following ultraviolet (UV) damage and is important for interstrand cross-link traverse (3)(4)(5)(6)(7). Other studies indicate that PRIMPOL can act as a TLS polymerase in the presence of bulky adducts, prevents RNA-DNA hybrid (R-loop) formation, and is important for tolerance of G4quadruplex accumulation by repriming downstream from this obstacle (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%